Single Undertaking, Different Speeds: Pliable Models for Decision-making in the WTO. (23rd May 2018) - Ansong, Alex
Abstract: The provisions on decision-making in the Marrakesh Agreement Establishing the World Trade Organization (WTO Agreement) have fundamental constitutional significance for the running of the WTO. The decision-making procedures established in Articles IX, X and XII of the WTO Agreement are therefore foundational to any discussion on reform of WTO decision-making and the creation of a more pliable system that is able to respond to the new and emerging challenges in the international trade regime. This article explores the provisions on amendments in Article X of the WTO Agreement and conducts analyses of how resort to the amendments provisions can possibly be used proactively to temper the current impasse-prone state of WTO decision-making. It also discusses the adoption of the Trade Facilitation Agreement in February 2017 and explores the possible lessons on decision-making that can be learnt from this landmark Agreement. The main theme that runs through the discussions in this article is the need to temper the rigid effects of single undertaking and consensus in WTO decision-making with more flexible mechanisms without the need for law reform.